2021
DOI: 10.1016/j.jiph.2021.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of lopinavir-ritonavir in COVID-19: A systematic review of randomized controlled trials

Abstract: Background Lopinavir-ritonavir is a repurposed drug for coronavirus disease-2019 (COVID-19). In this study, a pooled effect of lopinavir-ritonavir on mortality, virological cure, radiological improvement and safety profile in COVID-19 patients has been evaluated. Methods The databases were searched for comparative randomized controlled studies evaluating the efficacy and/or safety of lopinavir-ritonavir in COVID-19 patients. The mortality outcome was pooled as a risk di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 21 publications
(27 reference statements)
2
38
0
Order By: Relevance
“…Similar to the findings of Tobaiqy et al (38), our meta-analysis found higher adverse events in the lopinavir/ritonavir group compared with the control group. Also, in a study conducted by Patel et al (41), there was no difference in patients treated with lopinavir-ritonavir than supportive care, consistent with our study. A significant difference was observed between lopinavir/ritonavir and control groups for adverse events in the studies Tobaiqy et al (38) and Patel et al (41) authors observed more adverse events in lopinavir/ritonavir versus arbidol.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the findings of Tobaiqy et al (38), our meta-analysis found higher adverse events in the lopinavir/ritonavir group compared with the control group. Also, in a study conducted by Patel et al (41), there was no difference in patients treated with lopinavir-ritonavir than supportive care, consistent with our study. A significant difference was observed between lopinavir/ritonavir and control groups for adverse events in the studies Tobaiqy et al (38) and Patel et al (41) authors observed more adverse events in lopinavir/ritonavir versus arbidol.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with those of a meta-analysis published online in April 2021 where the differences between lopinavir/ritonavir group and those receiving standard therapy were not statistically significant in terms of mortality, viral clearance (RR = 1.06; 95% CI = 0.85–1.31) and radiological improvement (RR = 0.81; 95% CI = 0.62–1.05) [ 89 ].…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, drugs including lopinavir/ritonavir were associated with 4 × higher odds of liver injury ( 21 ). Of course it is noteworthy to imply that the efficacy of lopinavir/ritonavir in COVID-19 patients is still under question and should be evaluated in further studies ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%